Aluminium phosphide poisoning. Issue 1 (22nd December 2005) - Bogle, R G; Theron, P; Brooks, P; Dargan, P I; Redhead, J
Abstract : We describe a lethal poisoning in a healthy woman caused by deliberate ingestion of aluminium phosphide (AlP), a pesticide used to kill rodents and insects. Toxicity of AlP and review of cases reported to the National Poisons Information Service (London) 1997–2003 are discussed.